Natural Landmark Tracking Method to Support UAV Navigation over Rain Forest Areas - Pinagé, Felipe; Carvalho, José Reginaldo Hughes; Queiroz Neto, José Pinheiro de (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2012)
Field application of unmanned aerials systems (UASs) have increased in the last decade, with special focus on missions in which there is any kind of risk for the crew. However, in some situations the lack of onboard pilots makes the mission execution a very difficult task. As an example one has long endurance missions over rain forest, and glacial areas, due to the uniform patterns. In this scenario an embedded vision system plays a critical role on both remotely operated and autonomous navigation modes. This paper presents an approach towards a vision system model able to track landmarks in forest areas, as a navigation support for UASs. This system consists of two main steps: (1) multiresolution decomposition and nonrelevant features suppression techniques based on wavelet; and (2) automatic control points identification and matching for sensed video frame and reference image. Preliminary results demonstrated that this model can correctly track a sequence of natural landmarks while suppressing nonrelevant features.